Perancangan Aplikasi Kompresi File PDF Dengan Menerapkan Algoritma Stout Code - Wardi, Indra (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
Human habits in collecting and exchanging data, one of which is in the form of PDF files, has an impact on limited storage space on computers. PDF files contain information in the form of PDF files and are widely used in the world of education, offices, companies and so on to create reports, assignments, papers, theses and others which will then be PDF files. Because the need for PDF files is very important, humans tend to collect data in the form of PDF files. In the process of exchanging data in the form of PDF files both online and offline, humans often unknowingly send and then store them in large and clear sizes, this causes the need for a large amount of storage media. The solution to solve this problem is to do compression. It is intended that the PDF file size becomes much smaller so that the PDF file transfer process is fast and can save storage space. There are several algorithms for compressing PDF files, but this study uses the Stout Code algorithm. After compressing the algorithm, then the results of the compression of the algorithm are based on several parameters such as Ratio Of Compression (RC), Compression Ratio (CR), Space Saving (SS). The results of the Stout Code compression algorithm will be compressed and a compressed PDF file will be obtained.